The effect of estrous detection using visual observation and progesterone test kits on conception rate in cows - Soenmez, Mustafa; Tuerk, Gaffari; Demirci, Esref (Ankara Univ Press, 2007)
This study was conducted to compare the efficiency of estrous detection using visual observation and determination of progesterone levels by progesterone test kits in field condition, and to investigate whether the progesterone tests has positive effect on conception rate of cows. A total of 136 cows were used in this study. Cows were visually observed, and the behavioural signs of estrous were recorded. They were divided into three subgroups considering the intensity of estrous behaviour. Progesterone levels in serum samples were determined by progesterone test kits. Cows were also divided into three subgroups according to the progesteron levels, and then, all cows were inseminated artificially. The conception rates were determined by rectal palpation on 55-60(th) days following artificial insemination. The mean overall conception rate obtained from inseminations was recorded as 65.4 % in this study. It was found that the conception rate of cows which showed strong signs of estrous (76.5 %) was significantly higher (p<0.05) than that of cows exhibited no signs (53.7 %). It was observed that the conception rates (78.5 %) in cows which had low concentrations of progesterone (<1 ng/ml) during insemination was significantly (p<0.05) higher than that (23.8 %) of cows which had intermediate concentrations of progesterone (1-2.5 ng/ml). In addition, the conception didn't occur in cows which had high concentrations of progesterone (>2.5 ng/ml). In conclusion, progesterone test kits can be used to avoid errors in heat detection and to obtain higher conception rate from cows whose behavioural signs of estrous are not apparent through visual observation.
Keywords: conception rate; cow; estrous detection; progesterone level; visual observation